Mapping research in the Journal of Innovation & Knowledge to sustainable development goals - Raghu Raman; Debidutta Pattnaik; Krishnashree Achuthan; David Laurie Hughes; Adil S. Al-Busaidi; Yogesh K. Dwivedi; Maneesha Vinodini Ramesh; Prema Nedungadi (Journal of Innovation & Knowledge (JIK), 2024)
This study critically evaluates the contributions of the Journal of Innovation & Knowledge (JIK) toward advancing research aligned with the Sustainable Development Goals (SDGs), employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol for systematic literature review. We meticulously examine JIK's interdisciplinary research patterns, thematic focuses, and topic evolution, emphasizing the journal's engagement with SDG 9 (Industry, Innovation, and Infrastructure), SDG 8 (Decent Work and Economic Growth), and SDG 4 (Quality Education). By utilizing advanced techniques such as co-citation mapping and BERTopic modeling, this study identifies six major topics within the JIK, aligning with specific SDGs: 'EcoTech Revolution' highlights 'green technology,' 'Entrepreneurial Innovation' focuses on 'innovation management,' 'Economy 4.0' centers on 'digital transformation,' 'Effectual Innovation' involves 'technological innovation capability,' 'Collaborative Economy' addresses 'sharing economy sustainability,' and 'Green Innovation' explores 'eco-innovation.' These topics underscore JIK's role in advancing interdisciplinary research across key areas such as technology, entrepreneurship, the digital economy, practical innovation applications, collaborative consumption models, and environmental sustainability. Our findings highlight gaps, particularly in addressing SDG 5 (Gender Equality) and SDG 15 (Life on Land), presenting opportunities for JIK to diversify its research agenda toward a more inclusive sustainability discourse. Contributions from a global array of authors underscore JIK's international impact and its role in fostering diverse sustainability perspectives.
Keywords: O30; Q01; 650; Sustainable development goal; Innovation; Knowledge; Digital transformation; Entrepreneurship; Topic modeling; Citation clusters